Escaping irreproducible research practices and spreading awareness through education and (re-)training. (12th April 2022) - Lengger, Bettina; Johnston, Luke W.
Abstract : Many aspects of doing a PhD feel like being thrown into the ocean without any help or support. This is especially the case when it comes to doing data analysis and coding. Unsurprisingly, as a PhD student you end up being inefficient with time and effort when it comes to doing your work. Sadly research culture currently doesn't appreciate, fund or support these aspects of science as much as would be required to solve these problems. One of the first steps to changing this culture is through training and education of PhD students and early career researchers. Taking a course on being reproducible and open can lead you to being more productive and less stressed and, over time, teaching courses like these can help spread the awareness of these issues and slowly improve research culture.